2016
DOI: 10.1002/jms.3785
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the labile interactions of proteins and ligands using electrospray ionization mass spectrometry combined with a mathematical method

Abstract: represent the intensities of P, PL, PL ref and PLL ref at +n charge state, respectively. According to the measured R values and initial concentrations of protein ([P] o ) and ligand ([L] o ), Ka PL can be calculated by Eqn (7): Scheme 1. Structures of baicalein, naringin and rutin. JMS lettersJournal of MASS SPECTROMETRY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Studies have shown that some complexes stabilized by hydrophobic interactions or ionic interactions in solutions were not stable during ionization. The in-source partial or complete dissociation of these PL complexes happened even under “gentle” ESI ionization conditions. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that some complexes stabilized by hydrophobic interactions or ionic interactions in solutions were not stable during ionization. The in-source partial or complete dissociation of these PL complexes happened even under “gentle” ESI ionization conditions. …”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been developed to avoid the in-source dissociation, such as hydrogen/deuterium exchange, affinity chromatography, cold spray ionization, competitive experiments, and diffusion measurements. The researchers also found that the introduction of some additives into PL solution could increase the survival probability of the labile PL complexes. , However, it is not easy to find a suitable additive to protect the labile PL complexes. Until now, only several effective additives have been found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of analytical techniques are available for the characterization of binding behavior of proteins with ligands, most of which are complex, costly and time‐consuming. Many of them need complicated analyte preparation such as X‐ray analysis, nuclear magnetic resonance‐, mass‐ and circular dichroism (CD) spectrometry . Among all analytical techniques, affinity capillary electrophoresis (ACE) has prevailed as a fast, precise and parsimonious method for binding studies between proteins and various ligands in the last years .…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of binding behavior between proteins and ligands is an essential field of biochemistry and also the basis of drug development . Various analytical techniques are well suited to study protein–ligand interactions, especially X‐ray analysis of cocrystallized proteins, nuclear magnetic resonance‐, mass‐ and circular dichroism (CD) spectroscopy . Almost all of these techniques require pure proteins and partly large amounts of samples.…”
Section: Introductionmentioning
confidence: 99%